The moderating effect of age on peer and parent social influences on adolescent substance use - Schiavon, Samantha (American University, 2016)
The purpose of the study was to determine whether family and peer risk and protective factors predicted alcohol, marijuana and cigarette use as well as alcohol-related problems among 6th, 8th, and 10th grade students. This study also determined whether age moderated the relation between family and peer influences and substance use outcomes. Results demonstrated that peer alcohol use, peer positive alcohol use attitudes, and family history of drug and alcohol problems were associated with higher alcohol, marijuana, and cigarette use, as well as alcohol-related problems. Conversely, parental monitoring and peer negative alcohol use attitudes were associated with lower alcohol, marijuana, and cigarette use, as well as alcohol dependence. Moderation analyses demonstrated that among older adolescents’ social risk and protective factors were associated with higher or lower substance use, respectively. However, younger adolescents’ reported lower substance use, regardless of the level of the social influence. Implications regarding prevention programs are discussed.